Individual Differences in Eye-Movements During Reading: Working Memory and Speed-of-Processing Effects - Matthew J. Traxler; Clinton L. Johns; Debra L. Long; Megan Zirnstein; Kristen M. Tooley; Eunike Jonathan (Bern Open Publishing, 2012)
Mathematical models of eye-movement control do not yet incorporate individual differences as a source of variation in reading. These models nonetheless provide an excellent foundation for describing and explaining how and why patterns of eye-movements differ across readers (e.g., Rayner et al., 2006). We focus in this article on two aspects of individual variation: global processing speed (e.g., Salthouse, 1996) and working-memory capacity (e.g., Just & Carpenter, 1992). Using Hierarchical Linear Modeling (HLM) (Raudenbush & Bryk, 2001), we tested the extent to which overall reading speed and working-memory capacity moderate the degree to which syntactic and semantic information affect fixation times. We found that working-memory capacity interacted with sentence-characteristic variables only when processing speed was not included in the model.